2004
DOI: 10.1111/j.1532-5415.2004.52172.x
|View full text |Cite
|
Sign up to set email alerts
|

Living Alone and Outpatient Care Use by Older Veterans

Abstract: In nonveteran older adults, living alone influences outpatient care use, but its importance in the veteran population has not been well studied. The aims of this study are to describe the use of outpatient care by older veterans who live alone versus those who live with others and determine whether living alone influences outpatient use by older veterans. The data come from the 2001 Veteran Identity Program Survey designed to measure Department of Veterans Affairs (VA) and non-VA outpatient care use. Univariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…This result is in contrast from a previous systematic review revealing that elderly who have social support were more likely to visit a physician than those without any or less social support [34]. However, the finding of the present study was consistent with studies in the United States of America, which identified that elderly living alone were more likely to visit an out-patient unit and emergency department for advice or treatment [24] [25]. An elderly experiencing any form of sickness will opt to live with family members rather than be alone in order to better cope with serious illnesses and receive instrumental social support, informal care giving assistance, and use available resources at home from their household members [40].…”
Section: Association Between Living Arrangement and Health Facility Usupporting
confidence: 53%
See 1 more Smart Citation
“…This result is in contrast from a previous systematic review revealing that elderly who have social support were more likely to visit a physician than those without any or less social support [34]. However, the finding of the present study was consistent with studies in the United States of America, which identified that elderly living alone were more likely to visit an out-patient unit and emergency department for advice or treatment [24] [25]. An elderly experiencing any form of sickness will opt to live with family members rather than be alone in order to better cope with serious illnesses and receive instrumental social support, informal care giving assistance, and use available resources at home from their household members [40].…”
Section: Association Between Living Arrangement and Health Facility Usupporting
confidence: 53%
“…Many studies have shown that an elderly living alone was at a higher risk of becoming ill, having difficulty with instrumental activities of daily living, worsening mobility, and suffering from depression [22] [23]. Furthermore, evidences from developed countries indicated that those living alone or having weak social relationships showed higher likelihood of health facility utilization [24] [25] [26].…”
Section: Introductionmentioning
confidence: 99%
“…Those living alone were over represented in the multiple formal configuration. Studies have revealed the association between living alone and heavier outpatient care use in relation to lack of care at home (Guzman, Sohn, & Harada, 2004). In our sample, those in the multiple formal configuration used more psychosocial services including meal, socialization, and transportation services than others.…”
Section: Discussionmentioning
confidence: 82%
“…Predictors were chosen a priori based on a comprehensive review of the literature to identify potential confounders that may influence benzodiazepine use, including sociodemographic characteristics (i.e., age, education, gender, race, and marital status), history of anxiety/depression, and total number of medications [ 18 21 ].…”
Section: Methodsmentioning
confidence: 99%